Enhancement in Watermarking Approach Using DCT-DWT-SVD Techniques by Applying Kalman Filter - Khushbu,; Kaur, Deepinder (International Journal of Computer Sciences and Engineering, 2025)
With the rapid growth of internet the various digital methods has been proposed to protect the multimedia information from the non authorized accesses use and change. Among all the proposed methods the watermarking technique is the most common technique for protecting the multimedia data for unauthorized access. There are various algorithms for watermarking. The DCT-SVD based technique takes more processing time and has less capacity and imperceptibility. To increase the efficiency of SVD technique the DWT and SVD methods are combined and new method is generated which has less processing time and more robust to different type of security attacks. But the proposed hybrid algorithm is more robust to security attacks due to which the PSNR values have been increased. Then we will apply kalman filter to increase the PSNR value by removing noise.